Microplastic Contamination in Waters and Sediments in the Selorejo Reservoir, Malang Regency, East Java - Prahardika, Bayu Agung; Akbar, Iqbal Fatkhul; Muzammil, Muhammad Imam (Universitas Brawijaya, 2023)
Microplastic waste particles are a new contamination material in aquatic and terrestrial ecosystems. Heaps of garbage and fishing activities around residential areas are examples of anthropogenic activities around the Selorejo Reservoir and can potentially become sources of microplastic contamination. This research aims to observe the presence of microplastic contamination type and its abundance in water and sediment samples taken from the Selorejo Reservoir. The purposive sampling method was applied at five different stations, including the Konto River inlet, Kwayangan River inlet, residential area (kauman hamlet), tourism area, and reservoir outlets. Each station has three transects (as replicates), and about 100 liters of water and 1000 grams of sediment were taken. Water and sediment samples were then destruction using 30% H2O2 acid and 30% H2SO4 to remove organic components that were still attached and later facilitated observation under a stereo microscope with a magnification of 400X to make it clearer. All types of microplastics found were then counted based on their respective numbers. The analysis results showed that there was microplastic contamination in the reservoir water samples at each station. The highest abundance of microplastics was successively found in the Konto River inlet with a total abundance value of 39.27x101 particles/liter, then in the residential area (kauman hamlet) a number of 35.34x101 particles/liter, tourist areas 33.67x101 particles/liter, outlet 30.36x101 particles/liter and Kwayangan river inlet 29.67x101 particles/liter. Meanwhile, the presence of microplastics was also found in reservoir sediment samples. The highest abundance of microplastics was also found in sediments in the Selorejo Reservoir originating from the Konto River inlet with a total abundance value of 3.68 particles/gram, then in the tourist area 2.08 particles/gram, in the Kwayangan River inlet 1.56 particles/gram, in the residential area a number of 1.2 particles/gram and outlets 1.12 particles/gram. The types of microplastic found in the waters of the Selorejo Reservoir include fibers, fragments, and filaments. While the types of microplastics found in Selorejo Reservoir sediments include fibers, fragments, filaments, and films. This result is related to the existence of various community activities which are sources of microplastic contamination.